Mental health and well-being of fathers of children with intellectual disabilities: systematic review and meta-analysis - Kirsty Dunn; Deborah Kinnear; Andrew Jahoda; Alex McConnachie (BJPsych Open, 2019)
BackgroundCaring for a child with intellectual disabilities can be a very rewarding but demanding experience. Research in this area has primarily focused on mothers, with relatively little attention given to the mental health of fathers.AimsThe purpose of this review was to summarise the evidence related to the mental health of fathers compared with mothers, and with fathers in the general population.MethodA meta-analysis was undertaken of all studies published by 1 July 2018 in Medline, PsycINFO, CINAHL and EMBASE, using terms on intellectual disabilities, mental health and father carers. Papers were selected based on pre-defined inclusion and exclusion criteria.ResultsOf 5544 results, 20 studies met the inclusion criteria and 12 had appropriate data for meta-analysis. For comparisons of fathers with mothers, mothers were significantly more likely to have poor general mental health and well-being (standardised mean difference (SMD) −0.38, 95% CI −0.56 to −0.20), as well as higher levels of depression (SMD, −0.46; 95% CI −0.68 to −0.24), stress (SMD, −0.32; 95% CI −0.46 to −0.19) and anxiety (SMD, −0.30; 95% CI −0.50 to −0.10).ConclusionsThere is a significant difference between the mental health of father and mother carers, with fathers less likely to exhibit poor mental health. However, this is based on a small number of studies. More data is needed to determine whether the general mental health and anxiety of father carers of a child with intellectual disabilities differs from fathers in the general population.